GASTRO-RETENTIVE SUSTAINED RELEASE MUPS (MULTI-UNIT PARTICULATE SYSTEM) OF RIVAROXABAN FOR ORAL ADMINISTRATION - S. VERMA, PRAVEEN KUMAR; SONI, PRAKASH K.; SONI, REENA; PASWAN, SURESH K. (International Journal of Applied Pharmaceutics, 2026)
Objective: This study focuses on the development and evaluation of gastro-retentive multi-unit particulate systems (MUPS) by utilizing fluidized bed coater, for the oral delivery of rivaroxaban, a direct oral anticoagulant (DOAC). Methods: The method involves coating of three layers comprising the drug layer, effervescent layer, and polymer layer, each layer containing specific ingredients. These solutions were magnetically stirred, filtered, and coated onto sugar spheres (sucrose) using a Fluidized bed coater (FBC) (P+AM Glatt). The coated pellets were evaluated for parameters like particle size, friability, buoyancy, in vitro drug release, differential scanning calorimetry (DSC) analysis, scanning electron microscopy (SEM), and capsule filling performance. The method is designed in order to optimize the coating process and to assess the quality of pellets and enhance the drug delivery of rivaroxaban. Results: Batch N-IV (4% Eudragit NM 30D) achieved 84.8% sustained drug release over 24 h with minimal burst (20.85% at 1 h), fitting the Korsmeyer-Peppas model (R²=0.995, n=0.647). This formulation floated rapidly (2.15 min lag time) for>24 h, and exhibited excellent physical properties (friability: less than 1%; Carr’s index: 0.842%; Hausner ratio: 1.008), with high drug loading (17.11 mg/250 mg pellets), and high coating efficiency (98.6%). Conclusion: Compared to immediate-release formulations, the MUPS-based approach improved gastric retention, provide sustain release and improve dissolution profile along with a reduction in dosing frequency.